2010
DOI: 10.4314/gjpas.v16i3.62852
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of proximate composition of fruits of lycopersicon esculentum (roma vf) under stress and staking.

Abstract: The effects of salt (CaCl 2 ) and staking on the proximate composition of fruits of tomato (Roma VF) were studied at the Department of Botany Experimental garden, University of Uyo, Nigeria. Calcium chloride salt levels of 0, 50, 100, 150 and 200g per 4Kg of loamy sandy soil were used, with and without staking. The moisture, dry matter, ash, crude fat, crude protein, carbohydrate and crude fibre contents in treatment with calcium chloride/ staking were significantly (P<0.05) higher than those of calcium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In addition, ash was found more predominant in calcium chloride soaking samples (Table 1). Current outcomes were in agreement with the findings reported by Osim et al (2010). Lyimo et al (2010) reported that loss of nutrient composition in sweet potato during processing depended on varieties, as some varieties are more tolerant to certain processing techniques than others.…”
Section: Changes In Proximate Compositionsupporting
confidence: 91%
“…In addition, ash was found more predominant in calcium chloride soaking samples (Table 1). Current outcomes were in agreement with the findings reported by Osim et al (2010). Lyimo et al (2010) reported that loss of nutrient composition in sweet potato during processing depended on varieties, as some varieties are more tolerant to certain processing techniques than others.…”
Section: Changes In Proximate Compositionsupporting
confidence: 91%
“…This low nutrient composition in L2 location relative to L1 may be attributed to poor topography terrains that characterized the soil of L2 sampling location, together with environmental problems such as flooding and intense riverine setting of the habitat [4]. Eco-physiological influenced changes in plants elemental composition have been reported [32,33]. Several factors such as age, cultural practices, environment, the season and the varieties have been reported to influence the nutrient composition of plants [ 34 ].…”
Section: Discussion:-mentioning
confidence: 99%